BNT162b2 COVID‐19 vaccine and gynecologic emergency department visit diagnoses—A study from a large tertiary center. Issue 1 (1st December 2022) - Meyer, Raanan; Mohr‐Sasson, Aya; Mashiach, Roy; Levin, Gabriel
Synopsis: COVID‐19 vaccine is associated with higher rates of pregnancy of unknown location and a trend of increased vaginal bleeding.